Fenomena Fear of Missing Out (FoMO) dan Upaya Pemulihan Kesehatan Mental Siswa SMK di Kabupaten Buleleng Melalui Pendekatan Konseling Mindfulness: Sebuah Studi Fenomenologis - Ketut Manis Santi Purnami; I Wayan Lasmawan; Desak Putu Parmiti (LPPM Institut Pendidikan Nusantara Global, 2026)
The phenomenon of Fear of Missing Out (FoMO) is becoming increasingly prevalent among adolescents, particularly vocational high school (SMK) students in Buleleng Regency. Driven by the rapid expansion of social media and peer pressure, this condition is characterized by excessive anxiety and a compulsive need to remain digitally connected. FoMO significantly impacts mental health, triggering academic stress, sleep disturbances, and diminished self-esteem. This study aims to describe students' subjective experiences of FoMO, analyze its psychological consequences, and explore the effectiveness of mindfulness-based counseling as a recovery strategy. Methods: This qualitative phenomenological study involved SMK students in Buleleng exhibiting FoMO symptoms. Data were collected through in-depth interviews, observations, and documentation, then analyzed using data reduction, thematic categorization, and phenomenological interpretation to capture the deepest essence of the participants lived experiences. Findings: The results reveal that students perceive FoMO as a